Effectiveness of Positive Self Talk to Increasing Student’s Self-Confidence - Cempaka Putrie Dimala; Arif Rahman Hakim; Ivana Mara Salsabila (Edutran of Psychology and Behavior, 2023)
Currently the problem that often occurs in individuals, especially in early adulthood is regarding low self-confidence. As students, individuals must have self-confidence because students are required to actively become independent individuals, able to take the initiative to seek information and be able to communicate well in private situations and to the general public. This is in line with a preliminary study through a pre-research survey conducted by researchers regarding self-confidence in psychology students at Buana Perjuangan Karawang University class of 2018. Based on data from students, namely 40 respondents, the result was 32% of students felt less confident about appearing in class and often Avoid eye contact with the lecturer during class discussions. This is because some students do not dare to ask the lecturer directly. The urgency regarding self-confidence which tends to be low needs to be increased through positive self-talk. This study aims to determine the effectiveness of positive self-talk to increase the self-confidence of psychology students at Buana Perjuangan University, Karawang. This study used a one-group pre-test and post-test design. The population in this study were psychology students class of 2018. The sampling technique used was purposive sampling and the sample consisted of 11 students. The instrument used in this study is a self-confidence scale that has been tested starting from expert judgment to reliability testing. The reliability of the trust scale tested using Cronbach Alpha obtained a coefficient of 0.896 which indicates a very good level of reliability. Hypothesis testing using paired sample test assisted by SPSS version 23 for Windows. The results showed that the treatment with positive self-talk techniques was effective in increasing the self-confidence of psychology students. This can be seen in the paired sample test, the results of the experimental group's pretest and posttest scores obtained a Sig (2-tailed) value of 0.005 <0.05, which means H0 is rejected and HA is accepted.